Dampak Digitalisasi Pendidikan terhadap Kepemimpinan Kepala Sekolah - Anissaa Alhaqqoh Darwis; Helmina Helmina; Azainil Azainil (Journal on Education, 2024)
Recent studies show that successful leadership in the digital era requires principals who are visionary, collaborative, and capable of encouraging active participation from the entire school community in the use of technology. While many studies have explored the influence of such leadership on the digitalization of education, none have investigated the impact of educational digitalization on school principals' leadership. This study uses a literature review method with a descriptive-analytic approach, philosophical study, and qualitative-rationalistic approach, drawing from literature published in the last five years. The results indicate that the shift towards digitalization demands that principals be proficient in leading to integrate technology into education, manage technological infrastructure in schools, enhance their digital skills, promote continuous professional development for teachers, make data-driven decisions, use digital platforms to communicate information, and effectively address challenges arising from digitalization. The recommendation from this study is that as leaders, school principals must be sensitive to the changing times and the inherent needs.